(untitled) (Research, Society and Development, 2021)
Objective: To understand the main neurodevelopmental disorders related to alterations in the GRIN2B gene. Methodology: A descriptive and documentary case report was carried out. Data collection was carried out through specific tools such as interviews with a structured questionnaire, exams and forms that contained information on research identification; history of the disease under study; symptomatic interrogation; pathological family history; general physical examination and directed to organs and systems; diagnostic hypotheses; medical procedures already performed (exams and pharmacological and non-pharmacological treatment). Results: It was found that the patient in the case reported has Autosomal Dominant Intellectual Deficiency 6 (GRIN2B-Related Neurodevelopmental Disorder), based on their clinical characteristics and identification of the pathogenic variant in heterozygosity on chromosome 12 of the GRIN2B gene, excluding the possibility from other causes. Conclusion: The importance of GRIN2B in the development of the human brain is highlighted, allied to the understanding of the main neurodevelopmental disorders related to alterations in the GRIN2B gene, being of high relevance for the diagnosis and prognosis of these patients by contributing to the training of professionals capable of performing an early diagnosis, with knowledge of the clinical characteristics of the genetic alteration, immediate treatment measures, thus improving the quality of life and prognosis of these patients.